Adherence and Associated Factors of Treatment Regimen in Drug-Susceptible Tuberculosis Patients - Bea, Sungho; Lee, Hyesung; Kim, Ju Hwan; Jang, Seung Hun; Son, Hyunjin; Kwon, Jin-Won; Shin, Ju-Young (Frontiers in Pharmacology, 2021)
Background: Adherence to tuberculosis (TB) drugs is one of the key aspects of global TB control, yet there is a lack of epidemiological evidence on the factors influencing adherence to TB drugs. Thus, this study aimed to explore the adherence and factors associated with adherence among TB patients in South Korea. Methods: We conducted a cohort study using a sampled national healthcare database from 2017 to 2018. Our study population included incident TB patients initiating quadruple or triple regimen who were available for follow-up for 180-days. Adherence was evaluated using the proportion of days covered (PDC): 1) adherent group: patients with PDC≥80%; 2) non-adherent group: patients with PDC<80%. Kaplan-Meier analysis was conducted to calculate the median time-to-discontinuation in the study population. We calculated the adjusted odds ratios (aOR) with 95% confidence intervals (CI) to assess factors associated with adherence to TB drugs using logistic regression. Results: Of 987 patients, 558 (56.5%) were adherent and 429 (43.5%) were non-adherent, with the overall mean PDC of 68.87% (standard deviation, 33.37%). The median time-to-discontinuation was 113 days (interquartile range 96-136) in the study population. Patients initiating quadruple regimen were more likely to adhere in comparison to the triple regimen (aOR 4.14; 95% CI 2.78-6.17), while those aged ≥65 years (aOR 0.53; 95% CI 0.35-0.81), with a history of dementia (aOR 0.53; 95% CI 0.34-0.85), and with history of diabetes mellitus (aOR 0.70; 95% CI 0.52-0.96) were less likely to adhere to the drug. Conclusion: Approximately 45% of TB patients were non-adherent to the drug, which is a major concern for the treatment outcome. We call for intensified attention from the authorities and healthcare providers to reinforce patients’ adherence to the prescribed TB drugs.